Interleukin 15 Pharmacokinetics and Consumption by a Dynamic Cytokine Sink - Hangasky, John A.; Waldmann, Thomas A.; Santi, Daniel V. (Frontiers in Immunology, 2020)
Interleukin-15 (IL-15) is crucial for the proliferation and survival of NK and CD8+ T memory cells, and of significant interest in immuno-oncology. Immune cell expansion requires continuous IL-15 exposure above a threshold concentration for an extended period. However, the short t1/2 of IL-15 makes this impossible to achieve after a single injection without a high Cmax and toxicities. The most effective way to deliver IL-15 is continuous intra-venous infusion, but this administration mode is impractical. Efforts have been devoted to developing IL-15 agonists which after a single injection maintain the cytokine in a narrow therapeutic window for a long period. Enigmatically, although the half-life extension technologies used often extend the half-life of a protein to one or more weeks, the modified IL-15 agonists studied usually have systemic elimination half-lives of only a few hours and rarely much longer than one day. These short half-lives – common to all circulating IL-15 agonists thus far reported – can be explained by a dynamic increase in clearance of the agonists that accompanies target immune cell proliferation. What is needed is an IL-15 agonist that is as effective as continuous intravenous infusion, but with the convenience and acceptance of single injections at one-week or longer intervals.